1991
DOI: 10.7901/2169-3358-1991-1-395
|View full text |Cite
|
Sign up to set email alerts
|

Development of Corexit 9580—A Chemical Beach Cleaner

Abstract: Chemical beach cleaners can facilitate cleanups of oiled shorelines by improving the efficiency of washing with water. The improvement is a result of reduced adhesion of the oil coating, which makes it easier to remove from shoreline surfaces, thereby reducing washing time and lowering the temperature of the wash water needed to clean a given area. The criteria established for use of chemical beach cleaners in the Exxon Valdez spill cleanup included demonstrating enhanced cleaning with low levels of toxicity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The efficacy of additional oil removal using the SWA was greater for rock/cobble shorelines (56 ± 14% of the original mass of oil applied) compared to wetland shorelines with organic substrate (13 ± 3%). The degree of removal from rock/cobble shorelines, in our study, is similar to previous reports (26-65%) for hard substrates [8,9]. Lower efficacy in more organic substrates is also in agreement with prior studies.…”
Section: International Journal Of Environmental Sciences and Natural Resourcessupporting
confidence: 93%
See 1 more Smart Citation
“…The efficacy of additional oil removal using the SWA was greater for rock/cobble shorelines (56 ± 14% of the original mass of oil applied) compared to wetland shorelines with organic substrate (13 ± 3%). The degree of removal from rock/cobble shorelines, in our study, is similar to previous reports (26-65%) for hard substrates [8,9]. Lower efficacy in more organic substrates is also in agreement with prior studies.…”
Section: International Journal Of Environmental Sciences and Natural Resourcessupporting
confidence: 93%
“…Corexit EC9580A™ is a SWA but it can also be used as a herding agent to thicken oil slicks so that they can be ignited when in situ burning is being used as a removal method [7]. The product was developed during the Exxon Valdez oil spill response in the late 1980s and was intended for application to rocky or rip rap marine shores where it can increase recovery of stranded oil by up to 65% [8]. Removal from hard surfaces has been effective even when heavy oils have weathered for up to 4d [9][10][11].…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…A dispersant has been improved by reducing the adhesion of the oil coating, which makes it easier to remove from shoreline surfaces, thereby reducing washing time and lowering the temperature of the wash water needed to clean a given area [79]. A dispersant has been improved by reducing the adhesion of the oil coating, which makes it easier to remove from shoreline surfaces, thereby reducing washing time and lowering the temperature of the wash water needed to clean a given area [79].…”
Section: Special Chemicals For Oiled Shorelinesmentioning
confidence: 99%
“…Independently performed field tests in Prince William Sound and during the Morris J Berman Spill in Puerto Rico, have shown that surfactant-based shoreline cleaning agents can be successfully incorporated into a clean-up program (Fiocco, 1991;NOAA, 1994).…”
Section: Abstract: Surfactants Shoreline Cleaning Agents Temperatumentioning
confidence: 99%